The Effect of Nipple Stimulation on The Duration of The Second Stage of Labor at The Motolohu Health Center UPTD, Pohuwato Regency - Pingkan JB Walean; Anik Sri Purwanti; Rifzul Maulina (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2025)
The labor process in pregnant women can take place with varying times, and several factors can affect the duration of labor, one of which is nipple stimulation. Nipple stimulation is known to stimulate the production of oxytocin which helps accelerate uterine contractions and shorten the duration of labor, especially in the second stage. Therefore, this study aims to determine the effect of nipple stimulation on the duration of second stage labor in women giving birth at the Motolohu Health Center UPTD, Pohuwato Regency. This study aims to determine whether nipple stimulation can affect the duration of second stage labor in women giving birth at the Motolohu Health Center UPTD, Pohuwato Regency. This type of research is quantitative research with an experimental design using a pre-test and post-test approach. The study was conducted on 16 respondents who met the inclusion and exclusion criteria. Nipple stimulation was carried out during the active phase of labor to monitor changes in the duration of second stage labor. Data were analyzed using the Wilcoxon test with a significance level of 0.05. The results showed that after nipple stimulation, there was a significant change in the duration of the second stage of labor in mothers in labor. The p value obtained from the Wilcoxon test was 0.000, which indicated that nipple stimulation had a significant effect on reducing the duration of the second stage of labor. Nipple stimulation can shorten the duration of the second stage of labor in mothers in labor at the Motolohu Health Center UPTD, Pohuwato Regency. This shows that nipple stimulation can be used as an alternative to accelerate the labor process safely and effectively. It is hoped that nipple stimulation can be used as one of the non-pharmacological interventions that are routinely carried out in health facilities as an effort to accelerate the labor process. Further research with larger samples and long-term research is also needed to confirm these results